The Impact of Work Environment, Communication, and Rewards on Employee Performance at The Hajj Financial Management Agency - Hadianto, M. Sopian; Wahyuningtyas, Ratri (Jurnal Pendidikan Indonesia, 2025)
The management of hajj pilgrimage funds by the Government of Indonesia requires high professionalism and accountability. The declining trend in employee performance at the Hajj Financial Management Agency (BPKH) in 2022, marked by a reduction in "Outstanding" qualifications, highlights the need for improvements in the work environment, communication, and reward systems. This investigation intends to evaluate the impact of work environment, communication, and rewards on employee performance at BPKH. A quantitative approach was employed, collecting data through questionnaires distributed to 111 permanent employees, determined using Slovin's formula from a total population of 153. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reflect that work environment, communication, and rewards significantly affect employee performance. This research contributes to the development of human resource management literature, particularly in the public sector. The study recommends enhancing ergonomic work facilities, fostering transparent internal communication, and implementing performance-based reward systems. These strategies are expected to encourage employee adaptation, collaboration, and the creation of a work culture that sustainably improves employee performance at BPKH